2021
DOI: 10.1097/mlr.0000000000001504
|View full text |Cite
|
Sign up to set email alerts
|

Plan Type and Opioid Prescriptions for Children in Medicaid

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Specifically, we found that Medicaid patients had higher patient-reported opioid consumption and opioid refill rates over time compared with patients with private insurance or Medicare. This finding is consistent with previous literature highlighting inequities among Medicaid patients related to opioid prescribing and opioid-related morbidity, although these findings may be a proxy for important unmeasured characteristics among Medicaid patients . For example, disability, chronic disease, and surgical morbidity and mortality have historically been higher among Medicaid patients .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Specifically, we found that Medicaid patients had higher patient-reported opioid consumption and opioid refill rates over time compared with patients with private insurance or Medicare. This finding is consistent with previous literature highlighting inequities among Medicaid patients related to opioid prescribing and opioid-related morbidity, although these findings may be a proxy for important unmeasured characteristics among Medicaid patients . For example, disability, chronic disease, and surgical morbidity and mortality have historically been higher among Medicaid patients .…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with previous literature highlighting inequities among Medicaid patients related to opioid prescribing and opioid-related morbidity, although these findings may be a proxy for important unmeasured characteristics among Medicaid patients. 23 , 24 , 25 For example, disability, chronic disease, and surgical morbidity and mortality have historically been higher among Medicaid patients. 30 , 38 , 39 , 40 , 41 Medicaid beneficiaries are also more likely to report lower satisfaction and worse pain compared with privately insured patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations